Analysis and Presentation of Hospital Antibiogram from a Newly Established Tertiary Care Institute: A Step Towards Antimicrobial Stewardship - Singh, Dr.Sweta; Islahi, Dr.Sana; Sahu, Dr.Chinmoy; Gupta, Dr.Shefali; Kumar Srivastava, Dr.Niraj; Verma, Dr.Rajeev; Sen, Mr.Somdatt; Singh Taragi, Mr.Vikram (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Antimicrobial resistance (AMR) is emerging as a major global threat to public health of the recent times. The local antibiogram provides a guide to the clinicians and helps them choose the best empirical antimicrobial treatment according to the local antibiogram in the event when microbiology culture and susceptibility results are pending. It also helps in monitoring the trends of resistance to the common antimicrobials within the hospital set-up. Aims/Objectives: This study was planned to determine the prevalence rates of microbial isolates, to appraise and compare the local antibiogram of the newly established institute with established tertiary level centres. Materials & Methods: This cross sectional study was done for a period of 20 months and samples from outpatient as well as inpatients (from all the wards) were processed in the department of Microbiology. All the samples were processed, routine staining and biochemical tests were employed for preliminary identification of the isolates; followed by antibiotic sensitivity testing. Statistical analysis: The results were analysed using the SPSS version 22 software (SPSS Inc., Chicago, IL, USA). Results: The total no. of samples analysed during the specified time period was 20, 987. Overall culture positivity was seen as 36.5%; out of which 56 % was attributed to Gram negative bacteria and the rest by gram positive bacteria and fungal isolates. E.coli showed a sensitivity of 63% / 78% / 58% (AIIMS RBL/ICMR/Tertiary institute ) to Amikacin, Meropenem: 53/69/54 %, Imipenem: 62 / 64/ 61 %, Colistin: 98 /99/ 97 %. Klebsiella showed a sensitivity of 38/46/30 % (AIIMS RBL/ICMR/Tertiary institute) to Amikacin, Meropenem: 32/40/26 %, Imipenem: 39/43/30 %, Colistin: 93/96/92%. In the second line antibiotic sensitivity; Fosfomycin in E.coli showed 98%sensitivity, whereas for Klebsiella it was 94% and for pseudomonas 91%.56 % cases of MRSA were isolated in 2021-22 as compared to 54 % in 2022-23. Discussion: The analysed antibiogram suggests that urinary tract (UTIs), respiratory and pyogenic infections were the most common reasons for ordering culture and sensitivity tests in our setting. A lower percentage of sensitivity to amikacin, carbapenems and colistin as compared to the ICMR data was seen among the Gram-negative isolates of the present study. This might be related to the easy availability as over the counter medications and irrational use of these drugs in this study area. The predominant isolates in our study i.e.E. coli and Klebsiella spp. were resistant to the cephalosporins, aminoglycosides, etc.This reflected that the Multidrug resistant organisms isolated from various body site infections with resistance to third-generation cephalosporin and other routinely prescribed antibiotics is a major concern in this particular area of interest. Conclusion: This study provides an elaborately made antibiogram profile of approximately two years from the diagnostic microbiology laboratory of a newly established tertiary level institute catering to the needs of thousands of local population. Antibiotic policy along with local antibiogram is the stepping stone towards accreditation of any hospital setting as well as implementation of antimicrobial stewardship program.